Chemical modification/grafting of mesoporous alumina with polydimethylsiloxane (PDMS) - Pinheiro, Ana Filipa de Melo; Nijmeijer, Arian; Sripathi, Venkata Giri Prasad; Winnubst, Louis (European Journal of Chemistry, 2015)
A method for polydimethylsiloxane grafting of alumina powders is described which involves chemical modification of the surface of mesoporous (5 nm) γ-alumina flakes with a linker (3-aminopropyltriethoxysilane: APTES), either by a solution phase (SPD) or a vapour phase (VPD) reaction, followed by PDMS grafting. The systems were analysed by FTIR, gas adsorption/desorption and TGA. Grafting is proven by FTIR for all cases, meaning that a covalent bond exists between inorganic particle and organic moiety. It is demonstrated that the way of applying APTES (by SPD or VPD) has an effect on the morphology of linker as well as of PDMS. A more controlled grafting of the APTES linker on γ-alumina is possible by the VPD method, resulting in efficient grafting and good infiltration of PDMS in the pores of the inorganic system. Stability tests on these PDMS grafted alumina show no degradation after 14 days soaking in a wide range of solvents. Surface modification of metal oxide particles by organic moieties via a chemical reaction can adapt its interfacial properties and renders a high chemical stability of these inorganic-organic hybrids. This validates the use of these materials under severe applications like in membranes for solvent nanofiltration or for protein immobilization and resin modification in e.g. chromatographic applications.